2014
DOI: 10.1111/jvim.12462
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐α and Interleukin‐6 Concentrations in Cerebrospinal Fluid of Dogs After Seizures

Abstract: BackgroundIdiopathic and acquired epilepsy are common in dogs. Up to 30% of these dogs are refractory to pharmacological treatment. Accumulating experimental evidence indicates that brain immune response and presence of inflammatory mediators decrease the threshold for individual seizures and contribute to epileptogenesis.HypothesisDogs with seizures have higher cerebrospinal interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) concentrations compared to dogs with no seizures.MethodsA prospective double bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…patients with different seizure types reflected the severity of epilepsy (16)(17)(18). Dubé et al found that inflammatory cytokines (such as IL-1β) played a crucial role in epilepsy caused by febrile seizures in children (19).…”
Section: Figure 4 |mentioning
confidence: 99%
“…patients with different seizure types reflected the severity of epilepsy (16)(17)(18). Dubé et al found that inflammatory cytokines (such as IL-1β) played a crucial role in epilepsy caused by febrile seizures in children (19).…”
Section: Figure 4 |mentioning
confidence: 99%
“…Increased IL-1β was detected in the peripheral blood in dogs with epilepsy regardless of the cause [32]. In the CSF of dogs with naturally occurring seizures, significantly higher TNF-α and IL-6 concentrations were found [33]. In the forebrain of rats, IL-6 and TNF-α levels were increased after acute seizure, but only briefly, in contrast to IL-1β, which did not return to baseline levels even after the seizure had subsided [34].…”
Section: Inflammatory Mediators In Epilepsymentioning
confidence: 89%
“…Numerous studies have shown upregulation of IL-1β, IL-6, and TNF-α in animals with (recurrent) seizures (53)(54)(55)(56)(57)(58)(59) and patients with epilepsy (60)(61)(62)(63). IL-1β can affect neurotransmitter receptors (64,65), induce calcium influx by N-methyl-D-aspartate (NMDA) and 3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-mediated mechanisms in neurons (66,67), lead to alterations in expression of microRNAs in astrocytes (68)(69)(70), as well as potassium channels (71), metalloproteinases (72), altered astrocytic glutamate uptake (73,74) and calcium uptake (75), and induces astrocytic release of other pro-inflammatory cytokines (50).…”
Section: Figure 3 | Factors Involved In Astrogliosis (A)mentioning
confidence: 99%